2012
DOI: 10.1007/s13402-012-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 genetic variants are associated with platinum-based chemotherapy response and prognosis in patients with NSCLC

Abstract: The galectin-3 genetic polymorphisms of galectin-3 +292, rather than galectin-3 +191, were associated with the chemotherapy response and prognosis of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This was confirmed by Boer et al [9]. Besides, another study showed that for rs4652 in galectin-3, the OS of NSCLC patients with an AA genotype is significantly longer than that of those with a CC genotype; furthermore, CC genotype carriers have a worse chemotherapy response and NSCLC prognosis [16], which is in accordance with the present study. The association of galectin-3 SNP rs11125 with beta-lactam allergy may be related to the binding of galectin-3 to immunoglobulin E (IgE) [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was confirmed by Boer et al [9]. Besides, another study showed that for rs4652 in galectin-3, the OS of NSCLC patients with an AA genotype is significantly longer than that of those with a CC genotype; furthermore, CC genotype carriers have a worse chemotherapy response and NSCLC prognosis [16], which is in accordance with the present study. The association of galectin-3 SNP rs11125 with beta-lactam allergy may be related to the binding of galectin-3 to immunoglobulin E (IgE) [21].…”
Section: Discussionsupporting
confidence: 92%
“…The presence of SNPs in relevant genes, their target binding sites, and processing machinery can affect cancer risk, patient prognosis, and treatment efficacy [15]. 1 study explored the correlation of galectin-3 SNPs with chemotherapy response and also the prognosis and treatment parameters of non-small cell lung cancer (NSCLC) [16]. It was verified that the SNP rs4644, coding for the protein galectin-3, affected galectin-3' susceptibility to cleavage by matrix metalloproteinases, providing guidance for future clinical therapy of breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Patient responses to treatment were determined by the WHO criteria [18], which classify the response into four categories: complete response (CR), partial response (PR), stable disease (SD), and progressive disease [19]. CR and PR were combined as responders, and SD and PD were grouped as non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…All patients had received platinum-based chemotherapy after diagnosis (Table 1). The inclusion and exclusion criteria were described previously elsewhere [21]. The study was approved by the ethics committees of our hospital and written informed consent was obtained from each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Patient responses to treatment were determined after four cycles by the WHO criteria [21], which classify the response into four categories: complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD). CR was defined as complete disappearance of all measurable lesions.…”
Section: Methodsmentioning
confidence: 99%